Starch Nanomaterial as an Effective Biosorbent for the Removal of Toxic Pb (II) Ions from Aqueous Solution: Kinetics and Isotherm Study - Bilal Bhat; Laxmi Dubey; Harendra Sharma (Journal of Water and Environmental Nanotechnology)
In this study, we prepared the starch nanomaterial for the removal of toxic lead ions from aqueous solution. Different characterization techniques like X-ray diffraction, Scanning electron microscopy, Energy dispersive spectroscopy, Transmission electron spectroscopy, Particle size analysis (PSA), Fourier transform infra-red and BET were employed to investigate the characteristic properties of the prepared starch nanomaterial. PSA & TEM study shows the size of extracted starch is reduced to nano level by acid hydrolysis. The average particle size of acid hydrolyzed starch was found to be 85 nm. EDS spectra shows that no extra peaks related with any impurity was detected in the spectra of prepared starch nanomaterial. The prepared potato starch nanomaterial was used for the removal of Pb2+ ions from aqueous solution by adsorption process. In this study, the effect of different parameters was investigated using the batch adsorption procedure. Based on the experimental results, better adsorption efficiency was found at pH 6 and at contact time of 90 minutes (~93.49 %). Freundlich and Langmuir isotherm models were used for evaluating the equilibrium adsorption data. The equilibrium adsorption data displayed good fit values (R2 = 0.917 and 0.911, respectively) for both the Freundlich and Langmuir models. An excellent description of the kinetics was provided by the pseudo-second order kinetic model (R2 > 0.98). The data showed that the starch nanomaterial could be used as economical, highly productive, and promising adsorbent for the removal of heavy metals.